Structural solutions impact on thermal energy efficiency of heating surface at an open space - Kaczorek, Dobrosława; Koczyk, Halina (Journal of Civil Engineering and Management, 2013)
This paper presents studies on thermal energy efficiency of heating surface at an open space according to structural solutions and climatic conditions. Numerical simulation research was conducted to assess three different types of heating surfaces at an open space over chosen period of time in real weather conditions. Performance parameters such as surface temperature, supply temperature and efficiency of heating surface relative to constructional designs and model of control strategy used were analysed. The number, thickness and type of material layers beneath ground level were modified. The distance between heating pipes and their diameters were kept constant. The carried out analyses show that the used solutions can lead to significant differences in the performance and consequently in the energy efficiency of the heating system for open spaces.